2014
DOI: 10.1164/rccm.201401-0178oc
|View full text |Cite
|
Sign up to set email alerts
|

The Nonallergic Asthma of Obesity. A Matter of Distal Lung Compliance

Abstract: Rationale: The pathogenesis of asthma in obesity is poorly understood, but may be related to breathing at low lung volumes.Objectives: To determine if lung function in obese patients with asthma and control subjects would respond differently to weight loss.Methods: Lung function was evaluated by conventional clinical tests and by impulse oscillometry in female late-onset, nonallergic patients with asthma and control subjects before, and 12 months after, bariatric surgery. Measurements and Main Results:Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 35 publications
10
127
1
4
Order By: Relevance
“…Impedance from 5 to 35 Hz (Figures 2A and 2B) was fit with a two-compartment model featuring the compliance of both the peripheral lung and the central airways ( Figure 2C). The individuals with asthma started out before weight loss with larger values of peripheral elastance compared with the control subjects, and weight loss caused peripheral elastance to decrease by 60% in the those with asthma but only by 27% in the control subjects (51). The implication of these findings is that those with LONA obese asthma are distinguished from obese control subjects by having unusually collapsible airways that cause their lung functions to become especially compromised when lung volumes are reduced by obesity.…”
Section: Nature Of Obese Asthmamentioning
confidence: 90%
See 1 more Smart Citation
“…Impedance from 5 to 35 Hz (Figures 2A and 2B) was fit with a two-compartment model featuring the compliance of both the peripheral lung and the central airways ( Figure 2C). The individuals with asthma started out before weight loss with larger values of peripheral elastance compared with the control subjects, and weight loss caused peripheral elastance to decrease by 60% in the those with asthma but only by 27% in the control subjects (51). The implication of these findings is that those with LONA obese asthma are distinguished from obese control subjects by having unusually collapsible airways that cause their lung functions to become especially compromised when lung volumes are reduced by obesity.…”
Section: Nature Of Obese Asthmamentioning
confidence: 90%
“…This being the case, that which distinguishes those with LONA obese asthma and those with EOS obese asthma may be the way in which they respond to reduced lung volume. We recently uncovered a clue as to what this might be by measuring respiratory system impedance in individuals with LONA obese asthma and obese control subjects both before and after major weight loss achieved through bariatric surgery (51). Impedance from 5 to 35 Hz (Figures 2A and 2B) was fit with a two-compartment model featuring the compliance of both the peripheral lung and the central airways ( Figure 2C).…”
Section: Nature Of Obese Asthmamentioning
confidence: 99%
“…49,50 Decreased lung volumes increase airway reactivity, 51 perhaps through effects on airway smooth muscle. 52 The tendency toward early airway closure may also manifest during bronchoconstriction 53,54 and contribute to the increased dyspnea symptoms reported by obese asthmatics in comparison to their lean counterparts. We have found that obese asthmatics tend to have a less compliant lung periphery, which improves with weight loss.…”
Section: -45mentioning
confidence: 99%
“…We have found that obese asthmatics tend to have a less compliant lung periphery, which improves with weight loss. 54 The cause of this stiff periphery is not known, but could be related to airway closure, as sensitivity to airway closure decreases with weight loss. 55 Changes in lung function with decreased lung volumes and increased airway closure likely contribute significantly to the development of poorly controlled asthma in obesity.…”
Section: -45mentioning
confidence: 99%
See 1 more Smart Citation